PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP RESPON INVESTOR DALAM SEKTOR PERDAGANGAN, JASA, DAN INVESTASI - Budiman, Adrian (Business Accounting Review, 2015)
The purpose of this study is to determine whether there are significant implementation of corporate social responsibility which is measured using the global reporting initiative 3.1 towards the investor response as measured using the abnormal return. The sample used in this study were 324 company years in the trade, services, and investment in the research period of 2008-2012. The results of this study demonstrate that corporate social responsibility has positive effect on abnormal returns. While the results of the control variables, namely return on assets, the size of the company, debt to equity ratio, and the market share does not affect the abnormal return.